Mycobacterium chelonae cutaneous infection in a patient with mixed connective tissue disease - Renan Lage; Danilo Guerreiro Zeolo Biccigo; Felipe Borba Calixto Santos; Erica Chimara; Elisangela Samartin Pegas Pereira; Adilson da Costa (Anais Brasileiros de Dermatologia, 2015)
Around 50 mycobacteria species cause human disease. Immunosuppressive states predispose to non-tuberculous mycobaterium infection, such as Mycobacterium chelonae: AFB, non-tuberculous, fast growth of low virulence and uncommon as a human pathogen. It may compromise the skin and soft tissues, lungs, lymph nodes and there is also a disseminated presentation. The diagnosis involves AFB identification and culture on Agar and Lowenstein-Jensen medium base. A 41-year-old female with MCTD (LES predominance) is reported, presenting painless nodules in the right forearm. She denied local trauma. Immunosuppressed with prednisone and cyclophosphamide for 24 months. Lesion biopsy has demonstrated positive bacilloscopy (Ziehl-Neelsen stain) and M.chelonae in culture (Lowenstein-Jensen medium base), therefore clarithromycin treatment has been started (best therapy choice in the literature).